PELAYANAN SOSIAL TERHADAP LANSIA TERLANTAR DI PANTI JOMPO GRAHA WERDHA MARIE JOSEPH PONTIANAK - Victoria Novita Sari; Arkanudin Arkanudin; Annisa Rizqa Alamri; Brigita Anjelita; Maria Ernes Femia; Lusia Wini Lina Sari (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
Social services for the elderly or elderly people are still rarely discussed from the perspective of social workers as the scientific discipline that covers them. This problem has an impact on social services for the elderly which are still not holistic, so previous studies have not been able to find the basic needs, basic concepts, and basic patterns of this social work sector. This study will further explore social services for the elderly at the Graha Werdha Marie Joseph Nursing Home in Pontianak through the perspective of social workers. Data was collected through two data search techniques, namely non-participant observation and in-depth interviews. The results of the research show that the forms of social services provided by social workers in nursing homes include providing decent and comfortable accommodation, providing life insurance in the form of health, food, clothing and other necessities, carrying out recreational activities, and providing guidance. religious, mental and social. The basic needs of the elderly are to fulfill their living needs from the moment they arrive at the nursing home until the end of their life. The concept of social services for the elderly is charitable, that is, social workers provide social resources unilaterally. Meanwhile, the basic pattern of social services for the elderly is assessing the needs of the elderly, planning and implementing